Jean-Sébastien Bach - Geiringer, Karl 1899-1989; Celli, Rose (Paris Seuil, 1970)
This basic, one-volume study of Johann Sebastian Bach combines a sensitive biographical sketch with a detailed analysis of each of his major types of composition, including vocal music, organ music, keyboard music, and instrumental music. In each section, Geiringer thoroughly examines many Bach compositions and evaluates them in relation to the rest of the composer's work, as well as in relation to the music of his contemporaries. More than seventy musical examples enable the reader to understand how Bach worked and to observe his music in various stages of completion. In addition, an interesting aspect of research methods is revealed through an explanation of the techniques used in studying handwriting, paper, and watermarks in the original sources.
Keywords: Bach, Johann Sebastian -- 1685-1750; 18th Century (1701-1800); Composer; Biography; Germany